The Association Between Smoker Protection Laws and Smoking, Employment, and Attempting to Quit Smoking. - Moges, Rebeka; Iaria, Ruby; Lent, Adrienne B. (Tobacco Use Insights, 2026)
Background: Globally, workplaces have introduced non-smokers-only hiring policies to avoid hiring people who smoke since they cost thousands of dollars more annually to employ compared to non-smokers. Tobacco industry efforts gave rise to state smoker protection laws in the United States (U.S.), which protect people who smoke from employment discrimination. Objectives: This study examined the association between living in a state with a smoker protection law and smoking status among U.S. adults and employment status and attempting to quit smoking in the past 12 months among those who currently smoke. Design and Methods: Cross-sectional, nationally representative data from the 2015 – 2018 Behavioral Risk Factor Surveillance System were analyzed. Participants were U.S. adults who reported being unemployed or employed for wages. Unadjusted and adjusted logistic regression models controlling for race/ethnicity, income, education, health insurance, state, and sex assessed associations between living in a state with a smoker protection law and smoking status (n = 678,203) and employment status and attempting to quit smoking in the past 12 months among people who currently smoke (n = 110,630). Interactions for income were assessed. Results: Smoker protection laws were not associated with smoking status in the overall sample (ORadj = 0.99, 95% CI: 0.89, 1.11) or employment among those who smoke (ORadj = 1.23, 95% CI: 0.92, 1.65). They were associated with a significantly higher odds of being employed (ORadj = 1.30, 95% CI: 1.06, 1.60) among those who smoke earning <$35,000. They were associated with a significantly lower odds of attempting to quit smoking among people who smoke (ORadj = 0.80, 95% CI: 0.66, 0.97), especially those earning <$35,000 (ORadj = 0.71, 95% CI: 0.53, 0.96) and $35,000-<$50,000 (ORadj. = 0.52, 95% CI: 0.32, 0.84). Conclusions: While smoker protection laws may promote employment among low-income individuals who smoke, they may reduce quit attempts. Policies should promote evidence-based smoking cessation treatments to support quit attempts among people who smoke.